The Effect of Two Stay Two Stray Cooperative Learning in Improving Social Studies Learning Outcomes on the Topics of Ocean Exploration, Imperialism, and Colonialism for Grade VIII Students at SMP Negeri 07 Semarang - Zidna Nadia Aula; Lukki Lukitawati (Journal of Educational Sciences, 2026)
The relatively low learning outcomes of students in social studies highlight the necessity for instructional innovations that encourage active learning and meaningful knowledge construction. This research was conducted to examine the impact of the Two Stay Two Stray (TSTS) cooperative learning model on students’ learning outcomes regarding the topics of ocean exploration, imperialism, and colonialism among grade VIII students at SMP Negeri 07 Semarang. A quantitative approach was applied using a quasi-experimental design with a nonequivalent control group. The sample consisted of two classes, the experimental and control class, with 31 students per class. Data collection was carried out through multiple-choice pretest and posttest instruments. The data were then analyzed using normality and homogeneity tests, an independent samples t-test, and N-gain analysis. The findings revealed a significant improvement in the experimental class, with the average score increasing from 67.61 to 88.26 (p < 0.001). Furthermore, the average N-gain percentage of 66.10% was categorized as moderate. The results suggest that the TSTS model has a positive and statistically significant effect on students’ social studies learning outcomes. Therefore, it can be considered an effective interactive learning strategy for classroom implementation.